2010
DOI: 10.1007/s00268-009-0333-7
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip and Palate as a Cost‐effective Health Care Treatment in the Developing World

Abstract: The absence of disability weights for untreated cleft lip and palate after the fifth year of life does not fit with the reality of living with an unrepaired cleft lip or palate. The authors conclude that secondary interventions alleviate disability and should enable an individual to approach a zero residual disability weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 15 publications
0
104
0
Order By: Relevance
“…Various nongovernment organizations that work in Haiti, such as Operation Smile and Resurge International (formerly Interplast), have observed that surgical resources such as equipped operating rooms, trained nurse anesthetists, scrub technicians, and support staff are limited in supply but are still comparatively available [20,24]. The OTCS program is planned to take place in hospitals that possess the human and physical resources to perform orthopaedic trauma surgery.…”
Section: Cost Assessmentmentioning
confidence: 99%
“…Various nongovernment organizations that work in Haiti, such as Operation Smile and Resurge International (formerly Interplast), have observed that surgical resources such as equipped operating rooms, trained nurse anesthetists, scrub technicians, and support staff are limited in supply but are still comparatively available [20,24]. The OTCS program is planned to take place in hospitals that possess the human and physical resources to perform orthopaedic trauma surgery.…”
Section: Cost Assessmentmentioning
confidence: 99%
“…Organizations such as Operation Rainbow and Mercy Ships have been effective in providing surgical care. The success of their medical missions can be attributed to overcoming the scarcity of resources and budget costs and overcoming cultural and language barriers (Magee, Burg, & Hatcher, 2010). The surgical outcomes of Operation Rainbow and Mercy Ships are comparable to high-income centers.…”
Section: Resolutionsmentioning
confidence: 99%
“…The surgical outcomes of Operation Rainbow and Mercy Ships are comparable to high-income centers. Being equipped with their own laboratories, equipment, and resources allows the organizations to provide various procedures in eye care, reconstruction, general, orthopaedic, oral, and mental health, and palliative care (Magee, Burg, & Hatcher, 2010).…”
Section: Resolutionsmentioning
confidence: 99%
“…The letter by Thakkar et al [1] mentions my article [2] but seemed to focus on Magee's article [3] rather than mine. The letter discusses the economics of ''missions'' and visiting surgeons.…”
Section: To the Editormentioning
confidence: 99%